Integration of Green Quality Function Deployment and Fuzzy Multi-Attribute Utility Theory-Based Cost Estimation for Environmentally Conscious Product Development - Dong, Chensong; Zhang, C.; Wang, B. (Not advised, 2003)
There are increasing global demands for environmental friendly products. Green Quality Function Deployment - III (GQFD - III) is an innovative tool aiding in the development of environmentally conscious products and processes. An improved version of GQFD - III, Green Quality Function Deployment - IV (GQFD - IV) has been developed in this study. Its improvement over GQFD - III is that the life cycle cost is estimated using the Fuzzy Multi-Attribute Utility Theory (FMAUT) method. FMAUT costing is an excellent cost estimation method at the early design stage in product development. It is more effective than other traditional methods because it does not require detailed data on manufacturing processes of the product and it can handle attributes with uncertainty and incompleteness in nature. In a case study, life cycle costs of coffeemakers were estimated with errors of less than 7% using this new cost estimation model. In GQFD - IV, with the considerations of quality, environment and cost, analytical hierarchy process (AHP) is used for product concept selection and is found to be effective.